Multiple occlusions in extracranial arteries in patients with aortic arch syndrome: is minimally invasive treatment still possible? Technical aspects of the treatment based on our own experience and a review of the literature - Piotr Kaszczewski; Tomasz Ostrowski; Rafał Maciąg; Michał Elwertowski; Witold Chudziński; Zbigniew Gałązka (Videosurgery and Other Miniinvasive Techniques)
Takayasu arteritis is a large vessel vasculitis of granulomatous nature and unknown aetiology affecting predominantly the aorta and its major branches, which may lead to ischaemic symptoms of many organs including the central nervous system. To decrease the risk of neurological complications and improve the quality of life, an arterial revascularisation may be necessary. The treatment options include pharmacotherapy as well as both open surgical and endovascular procedures, which has to be carefully chosen to obtain clinical success. There is an ongoing debate on the advantages, possibilities, and indications for implementing endovascular and open surgical methods, especially in high-risk patients. In this article we present our own experience in the treatment of an unusually complex and high-risk patient with multiple occlusion of supra-aortic branches, focusing on the technical aspects of the procedures and the decision-making process, as well as to confront with contemporary medical knowledge.